Cerebellar haemorrhage triggered by allergic reaction to maintenance haemodialysis in a patient with eosinophilia. Issue 2 (14th February 2023) - Seki, Yumika; Ishioka, Hirotaka; Miyazaki, Mariko; Okamoto, Koji
Abstract : We report a case of eosinophilia and an allergic reaction that caused a cerebellar haemorrhage. An woman in her 80s presented with headache, dyspnoea and vomiting with severe hypotension soon after switching the dialysis membrane, and a CT scan revealed cerebellar haemorrhage. In the subsequent clinical course, the patient developed an allergic reaction to multiple membranes and required corticosteroids to continue haemodialysis (HD). Pre-existing eosinophilia is a risk factor for cerebral infarctions and dialysis membrane allergy, which is a common feature in patients undergoing HD. Membrane switching and corticosteroid therapy must be considered in case of multiple membrane allergies.